Effects of 3-week repeated cold water immersion on leukocyte counts and cardiovascular factors: an exploratory study - Versteeg, Ninja; Clijsen, Ron; Hohenauer, Erich (Frontiers in Physiology, 2023)
Aim: This exploratory study aimed to investigate the effects of a 3-week repeated cold water immersion (CWI) intervention on leukocyte counts and cardiovascular factors (mean arterial pressure [MAP], heart rate [HR]) in healthy men. Methods: A total of n=12, non-cold-adapted men (age: 25.2±4.0 years; height: 177.8±5.6 cm; weight: 73.8±6.5 kg) were randomly allocated to the CWI or control (CON) group. The CWI group underwent a 3-week repeated CWI intervention (12min at 7°C, 4x/week). The CON group did not receive any cold exposure or therapy. Total leukocyte numbers and proportions (neutrophils, basophils, eosinophils, monocytes, lymphocytes) and cardiovascular factors (MAP, HR) were assessed at baseline and after the 3-week intervention period. Results: Total leukocyte count decreased in CWI (p=0.027, 95%CI: -2.35 to -0.20 x103/µL) and CON (p=0.043, 95%CI: -2.75 to -0.50 x103/µL). CWI showed a decrease in neutrophil number (p=0.028, 95%CI: -1.55 to -0.25 x103/µL) and proportion (p=0.046, 95%CI: -6.42 to 0.56%). In contrast, CON showed no significant change (p>0.05). No differences were found for other leukocyte subtypes in CWI or CON (all p>0.05). MAP (p=0.028, 95%CI: -17 to -8 mmHg) and HR (p=0.027, 95%CI: -7 to -2 bpm) were reduced in CWI, whereas CON showed no change (p>0.05). Conclusion: The results suggest no relevant effects of 3-week repeated CWI on leukocyte counts in healthy men. Due to methodological limitations, the effects on the investigated cardiovascular factors remain unclear. Further studies with larger sample sizes are needed to examine the effects on immune function and cardiovascular health.